Can Authorization Reduce Poverty among Undocumented Immigrants? Evidence from the Deferred Action for Childhood Arrivals Program - Catalina Amuedo-Dorantes; Francisca M. Antman (Institute for the Study of Labor (IZA), 2016)
We explore the impact of authorization on the poverty exposure of households headed by undocumented immigrants. The identification strategy makes use of the 2012 Deferred Action for Childhood Arrivals (DACA) program, which provided a temporary work authorization and reprieve from deportation to eligible immigrants. Using a difference-in-differences approach, we compare DACA-eligible to DACA-ineligible likely unauthorized immigrants, before and after the program implementation. We find that DACA reduced the likelihood of life in poverty of households headed by eligible individuals by 38 percent, hinting at the gains from even temporary authorization programs.
Keywords: J15; I32; 330; immigration; poverty; DACA